Continuity or discontinuity? Aquatic exploitation in the portuguese Estremadura during the Atlantic period: São Julião and Magoito shell middens as case studies - Sousa, Ana Catarina (2017)
The shell middens of São Julião and Magoito, located on the Atlantic coast of the Lisbon peninsula, are the only sites of the Portuguese Estremadura that feature occupations from the Atlantic period. These sites present occupations of the Early Mesolithic and successive reoccupations in the Late Mesolithic (S. Julião), the Early and Middle Neolithic (S. Julião, Magoito), Late Neolithic (Magoito), Chalcolithic (S. Julião), and Bronze Age (Magoito). There is a great continuity in site structure throughout these periods, which is very specialized for the specific and episodic exploitation of aquatic resources. The reoccupations are found in distinct loci, showing a horizontal stratigraphy. Continuities and/or discontinuities of settlement during the Boreal/Atlantic transition period in Central and Southern Portugal are matter of debate. The gap recorded in Estremadura, during the Atlantic period, is analyzed by taking into account the taphonomy, the state of research, the environment and an economic and social model. This paper attempts a review of the known data, but also presents new results for São Julião.